DETERMINANTS OF CONSUMER SATISFACTION AND INTENTION TOREUSE ONLINE FOOD DELIVERY SERVICES: Influence of E-Servqual, Utilitarian Value, and Sales Promotion - I Gst. Ngr. Jaya Agung Widagda K.; I Gusti Ayu Dewi Adnyani, Cok Istri Anastasia Wedari, Putu Laksmita Dewi Rahmayanti, I Gusti Ayu Tir (INTERNATIONAL JOURNAL OF SOCIETY REVIEWS, 2026)
The objective of this study is to elucidate the mediating effect of satisfaction on the relationship between e-service quality, utilitarian value, sales promotion, and the intention to reuse online food delivery services. The research population comprises individuals who utilize online meal delivery services in Denpasar City, with an undisclosed quantity. A purposive sampling strategy was employed to select a sample size of 210 individuals. The employed analytical methodology involves the utilization of Path Analysis through Structural Equation Modeling with Partial Least Squares (SEM-PLS). The findings of the study indicate that e-service quality, utilitarian value, and sales promotions exert a favorable and statistically significant impact on both consumer happiness and the desire to reuse online food delivery services. Similarly, it may be observed that satisfaction plays a partial mediating role in the relationship between e-service quality, utilitarian value, sales promotion, and reuse intentions. Hence, it is essential for service providers to continually enhance the quality of e-service quality, utilitarian value, and sales promotions to augment consumer satisfaction and foster the intention to reuse online meal delivery services.